Measurement of top quark pair production in association with a Z boson in proton-proton collisions at s=13 TeV - (:unkn) unknown (SPRINGER, 2020)
A measurement of the inclusive cross section of top quark pair production in association with a Z boson using proton-proton collisions at a center-of-mass energy of 13 TeV at the LHC is performed. The data sample corresponds to an integrated luminosity of 77.5 fb(-1), collected by the CMS experiment during 2016 and 2017. The measurement is performed using final states containing three or four charged leptons (electrons or muons), and the Z boson is detected through its decay to an oppositely charged lepton pair. The production cross section is measured to be sigma (ttZ) = 0.95 +/- 0.05 (stat) +/- 0.06 (syst) pb. For the first time, differential cross sections are measured as functions of the transverse momentum of the Z boson and the angular distribution of the negatively charged lepton from the Z boson decay. The most stringent direct limits to date on the anomalous couplings of the top quark to the Z boson are presented, including constraints on the Wilson coefficients in the framework of the standard model effective field theory.
Keywords: Hadron-Hadron scattering (experiments); Top physics; HELICITY FRACTIONS; CROSS-SECTION; ROOT-S=8; JETS; PLUS